Structure and Function of the ESG Advisory in the Czech Republic's Financial Sector : A Qualitative Inquiry into Practice - Drboutová, Valentýna (2025)
This thesis explores ethical challenges related to the provision of ESG consulting and financing by banks in the Czech Republic, in the context of the EU’s Corporate Sustainability Reporting Directive. It aims to assess the ethical, financial, and reputational implications of current practices. A mixed-methods approach was adopted, combining market research on ESG service offerings with semi-structured interviews conducted among corporate clients and experts. The research focuses on mapping ESG advisory models, identifying governance issues, and proposing relevant policy recommendations. The findings suggest that banks are key actors in the sustainability agenda due to legislation, but their ESG advisory practices remain uneven. The study highlights limited standardization, unclear boundaries between advisory and financing roles, and a general lack of formal safeguards to manage potential conflicts of interest. It concludes with recommendations to enhance transparency, clarify responsibilities, and support the credible integration of ESG in banking services.